Annual cycle of bats in a cave of Jebel Errwa, a sub-desert zone of central Tunisia - Ridha Dalhoumi; Patricia Aissa; Hamouda Beyrem; Stéphane Aulagnier (Tropical Zoology, 2019)
Bat use of the “Bat cave” of Jebel Errwa (central Tunisia) was studied over one year. A maximum of 650 bats were found during diurnal and nocturnal surveys. Maximum activity at emergence was reported in late spring and early summer when the cave was occupied by nurseries of Myotis punicus, Rhinolophus euryale, Rhinolophus mehelyi and Miniopterus schreibersii. Females gave birth in May in the largest, moistest and coolest room of the roost; young started to fly in June and left the cave in August. Despite frequent disturbance by visitors, “Bat Cave” of Jebel Errwa is one of the most important underground sites in central Tunisia and should be protected.